Convergence between Regulation of Carbon Utilization and Catabolic Repression in Xanthophyllomyces dendrorhous - Pilar Martinez-Moya (American Society for Microbiology, 2020)
ABSTRACT Xanthophyllomyces dendrorhous is a carotenogenic yeast with a singular metabolic capacity to produce astaxanthin, a valuable antioxidant pigment. This yeast can assimilate several carbon sources and sustain fermentation even under aerobic conditions. Since astaxanthin biosynthesis is affected by the carbon source, the study of carotenogenesis regulatory mechanisms is key for improving astaxanthin yield in X. dendrorhous. This study aimed to elucidate the regulation of the metabolism of different carbon sources and the phenomenon of catabolic repression in this yeast. To this end, protein and transcript levels were quantified by iTRAQ (isobaric tags for relative and absolute quantification) and transcriptomic sequencing (RNA-seq) in the wild-type strain under conditions of glucose, maltose, or succinate treatment and in the mutant strains for genes MIG1, CYC8, and TUP1 under conditions of glucose treatment. Alternative carbon sources such as maltose and succinate affected the relative abundances of 14% of the wild-type proteins, which were mainly grouped into the carbohydrate metabolism category, with the glycolysis/gluconeogenesis and citrate cycle pathways being the most highly represented pathways. Each mutant strain showed significant proteomic profile changes, affecting approximately 2% of the total proteins identified, compared to the wild-type strain under glucose treatment conditions. Similarly to the results seen with the alternative carbon sources, the changes in the mutant strains mainly affected carbohydrate metabolism, with glycolysis/gluconeogenesis and the pentose phosphate and citrate cycle pathways being the most highly represented pathways. Our results showed convergence between carbon assimilation and catabolic repression in the strains studied. Interestingly, indications of cooperative, opposing, and overlapping processes during catabolic regulation were found. We also identified target proteins of the regulatory processes, reinforcing the likelihood of catabolic repression at the posttranscriptional level. IMPORTANCE The conditions affecting catabolic regulation in X. dendrorhous are complex and suggest the presence of an alternative mechanism of regulation. The repressors Mig1, Cyc8, and Tup1 are essential elements for the regulation of the use of glucose and other carbon sources. All play different roles but, depending on the growth conditions, can work in convergent, synergistic, and complementary ways to use carbon sources and to regulate other targets for yeast metabolism. Our results reinforced the belief that further studies in X. dendrorhous are needed to clarify a specific regulatory mechanism at the domain level of the repressors as well as its relationship with those of other metabolic repressors, i.e., the stress response, to elucidate carotenogenic regulation at the transcriptomic and proteomic levels in this yeast.